2010
DOI: 10.1371/journal.pntd.0000604
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 Produced during Trypanosoma cruzi Infection Plays a Central Role in Regulating Parasite-Induced Myocarditis

Abstract: BackgroundChagas disease is a neglected disease caused by the intracellular parasite Trypanosoma cruzi. Around 30% of the infected patients develop chronic cardiomyopathy or megasyndromes, which are high-cost morbid conditions. Immune response against myocardial self-antigens and exacerbated Th1 cytokine production has been associated with the pathogenesis of the disease. As IL-17 is involved in the pathogenesis of several autoimmune, inflammatory and infectious diseases, we investigated its role during the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(83 citation statements)
references
References 53 publications
(57 reference statements)
4
78
0
1
Order By: Relevance
“…In an attempt to study the role of IL-17 in protection, a series of experiments were performed using IL-17A knock out mice, as well as anti-IL-17 treatment. Results showed that while increased IL-17 expression was associated with susceptibility to T. cruzi infection in a murine model using bradykinin receptor 2−/− mice (52), other studies have shown that mice treated with anti-IL-17 and IL-17−/− mice exhibited earlier mortality as compared to controls, and that inhibition of IL-17 also resulted in greater heart inflammation (51, 53). Studies of IL-17 expression in Chagas patients showed that indeterminate patients display a higher frequency of IL-17+ T cells as compared to cardiac patients (50).…”
Section: Host Immune Responses and The Establishment Of Pathology: Immentioning
confidence: 99%
“…In an attempt to study the role of IL-17 in protection, a series of experiments were performed using IL-17A knock out mice, as well as anti-IL-17 treatment. Results showed that while increased IL-17 expression was associated with susceptibility to T. cruzi infection in a murine model using bradykinin receptor 2−/− mice (52), other studies have shown that mice treated with anti-IL-17 and IL-17−/− mice exhibited earlier mortality as compared to controls, and that inhibition of IL-17 also resulted in greater heart inflammation (51, 53). Studies of IL-17 expression in Chagas patients showed that indeterminate patients display a higher frequency of IL-17+ T cells as compared to cardiac patients (50).…”
Section: Host Immune Responses and The Establishment Of Pathology: Immentioning
confidence: 99%
“…[23,24] Activation of CD4 + and CD8 + T cells that synthesize Th1 cytokines generally correlates with myocardial damage, at least in experimental models, and may be modulated by IL-17 and T regulatory cells. [21,25,26] During acute infection, mononuclear cells produce high levels of IFN-γ,[27] TNF-α and IL-6. [28]…”
Section: Inflammation Oxidative Stress and Fibrosismentioning
confidence: 99%
“…Recently it has been described that IL-17 plays a role in controlling the resistance of experimental T. cruzi infection by modulating the Th1 response, therefore regulating the extent of myocardial destruction induced by the parasite (Guedes et al 2010). Regarding that Treg cells of IND group are prompt to produce high levels of IL-17 and IL-10 is possible to speculate that this cell-type might contribute to modulate the inflammatory response during the asymptomatic infection.…”
Section: Figmentioning
confidence: 99%